Effectiveness and safety of a single freeze strategy of cryoballoon ablation of atrial fibrillation: an EHRA systematic review and meta-analysis. Issue 1 (19th July 2021) - Farkowski, Michal Miroslaw; Karlinski, Michal; Barra, Sergio; Providencia, Rui; Golicki, Dominik; Pytkowski, Mariusz; Anic, Ante; Chun, Julian Kyoung Ryul; de Asmundis, Carlo; Lane, Deirdre Anne; Boveda, Serge
Abstract: To conduct a systematic review and meta-analysis to compare the effectiveness and safety of cryoballoon ablation of atrial fibrillation (AF) performed using a single freeze strategy in comparison to an empiric double ('bonus') freeze strategy. We systematically searched MEDLINE, EMBASE, and CENTRAL databases from inception to 12 July 2020, for prospective and retrospective studies of patients undergoing cryoballoon for paroxysmal or persistent AF comparing a single vs. bonus freeze strategy. The main outcome was atrial arrhythmia-free survival and eligible studies required at least 12 months of follow-up; the primary safety outcome was a composite of all complications. Study quality was assessed using the Cochrane risk of bias tool and the Newcastle–Ottawa Scale. Thirteen studies (3 randomized controlled trials and 10 observational studies) comprising 3163 patients were eligible for inclusion (64% males, 71.5% paroxysmal AF, mean CHA2 DS2 -VASc score 1.3 ± 0.9). There was no significant difference in pooled effectiveness between single freeze strategy compared to double freeze strategy [relative risk (RR) 1.03; 95% confidence interval (CI): 0.98–1.07; I 2  = 0%]. Single freeze procedures were associated with a significantly lower adverse event rate (RR 0.72; 95% CI: 0.53–0.98; I 2  = 0%) and shorter average procedure time (90 ± 27 min vs. 121 ± 36 min, P  < 0.001). A trend for lower risk of persistent phrenic nerve palsy was observed (RR 0.61; 95% CI: 0.37–1.01; I 2  = 0%). The quality of included studies was moderate/good, with no evidence of significant publication bias. Single freeze strategy for cryoballoon of AF is as effective as an empiric double ('bonus') freeze strategy while appearing safer and probably quicker (PROSPERO registration number CRD42020158696).